2012
DOI: 10.1007/s12350-011-9483-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced septal glucose metabolism predicts response to cardiac resynchronization therapy

Abstract: In patients with non-ischemic cardiomyopathy, greater extent of septal glucose metabolic R-MM pattern, predicted response to CRT. This parameter may be useful for identifying patients who benefit from CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…In clinical studies, patients fast for a minimum of 6 h before scanning, with nondiabetic patients receiving an oral glucose load before 18 F-FDG injection and diabetic patients an insulineuglycemic clamp to ensure that baseline blood glucose levels are not significantly different (30)(31)(32). Kreissl et al (13) found that as in humans, fasting reduced cardiac 18 F-FDG uptake rates in mice by approximately 5-to 6-fold.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, patients fast for a minimum of 6 h before scanning, with nondiabetic patients receiving an oral glucose load before 18 F-FDG injection and diabetic patients an insulineuglycemic clamp to ensure that baseline blood glucose levels are not significantly different (30)(31)(32). Kreissl et al (13) found that as in humans, fasting reduced cardiac 18 F-FDG uptake rates in mice by approximately 5-to 6-fold.…”
Section: Discussionmentioning
confidence: 99%
“…21,31,32 This pattern has been observed early post-revascularization following AMI. 31 40 nonischemic cardiomyopathy, repetitive stunning, may be observed after post-MI revascularization 31 Anselm et al described that the reverse mismatch pattern was seen in 48% of patients who underwent early PCI, with perfusion-FDG PET performed in the first 10 days following revascularization. 31 They observed that reverse mismatch was more associated to regional wall motion abnormalities and was associated with shorter time to PCI.…”
Section: Flow-metabolism Patterns Post-infarction In Petmentioning
confidence: 99%
“…Это, вероятнее всего, связано с высокой разрешающей способностью данного метода и большей чувствительностью 18 F-ФДГ в идентификации жизне-способного миокарда. Так, перфузионно-метаболиче-ское исследование миокарда при помощи ПЭТ с хлори-дом 82 Rbи 18 F-ФДГ [14] продемонстрировало хорошую информативность (AUC=0,855, р=0,017) в прогнозе ответа на КТР у пациентов с ДКМП. Научной группой Hacker [15] установлено, что объем жизнеспособного миокарда, по данным ПЭТ с 18F-ФДГ, является пре-диктором эффективности КРТ с чувствительностью 83% и специфичностью 71% при значении дефекта метаболизма 9% (площадь под ROC кривой 0,88; p=0,007).…”
Section: результатыunclassified